2005
DOI: 10.1055/s-2005-864199
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Aspects of Obstructive Sleep Apnea

Abstract: The primary events of obstructed breathing during sleep, snoring and obstruction of the upper airway, cause hypoxemia, sleep fragmentation, and daytime sleepiness. Obstructed breathing during sleep can have negative effects on mental processes, behavior, and interpersonal relations. This article reviews some of the cognitive, emotional, and social aspects of obstructive sleep apnea in adults and children. Apnea is associated with cognitive impairments but these are generally mild. Most studies suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 81 publications
2
24
0
1
Order By: Relevance
“…Both excessive daytime sleepiness and nocturnal hypoxemia seem to equally contribute to cognitive deficits 60–62. Moreover, excessive daytime sleepiness has been mostly related to impairment in attention, vigilance, and memory function, while hypoxemia tends to correlate with deficits in EF 57,61. In this light, our findings are suggestive for a causative role of nocturnal hypoxemia in executive impairment, considering that the levels of subjective perceived daytime sleepiness are comparable with the normal control subjects ( P = 0.232).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Both excessive daytime sleepiness and nocturnal hypoxemia seem to equally contribute to cognitive deficits 60–62. Moreover, excessive daytime sleepiness has been mostly related to impairment in attention, vigilance, and memory function, while hypoxemia tends to correlate with deficits in EF 57,61. In this light, our findings are suggestive for a causative role of nocturnal hypoxemia in executive impairment, considering that the levels of subjective perceived daytime sleepiness are comparable with the normal control subjects ( P = 0.232).…”
Section: Discussionsupporting
confidence: 60%
“…In general, the most common documented cause of sleep related breathing disorders in children can be considered as upper airway obstruction, with prevalence for OSAS of about 1%–3%, and a peak prevalence between 2 and 8 years of age 49. The symptoms of OSAS include abnormal position during sleep,50–52 mood disorders,9,53–56 reduced quality of life, and cognitive problems57 at all ages. Moreover, considering the increasing prevalence of OSAS and neurocognitive and cardiovascular consequences, an objective evaluation with nocturnal monitoring for children with suspected OSAS has been recommended 58,59…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is well known that the characterization of disease severity should not be based only on the AHI, but also on clinical features (mainly the disease duration) which are often not easily measurable. Previous studies showed that impairment in attention, vigilance and memory function is mostly related to EDS, while hypoxemia correlates more with deficits in executive functions (Bédard et al ., 1991; Décary et al ., 2000; Engleman et al ., 2000; Brown, 2005). In our sample we found a negative correlation between EDS and verbal memory tests, while no significant correlation between oximetric data and executive functions tests was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Since sleep-related breathing disorders may occur at times of critical brain development in children, neuropsychological disorders may appear later and may be irreversible. 1,15,16 Adenotonsillectomy has been found to improve behaviour in most children, if obturation was the result of adenotonsillar hypertrophy. Three to 10 months after adenotonsillectomy, behavioural improvement occurred regardless of age, sex, parental education and income.…”
Section: Discussionmentioning
confidence: 98%